2020
DOI: 10.3390/ijms21239207
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Teeth Reduces the Inflammatory Response of Macrophages to Acid Dentine Lysate

Abstract: Particulate autogenous tooth roots are used for alveolar bone augmentation surgery; however, dental plaque may provoke an inflammatory response that may counteract the desired graft consolidation process. Traditional mechanical cleaning of extracted teeth may be of support to lower a possible inflammatory response of the autograft. To test this assumption, extracted porcine teeth were left either uncleaned or underwent mechanical cleaning with a toothbrush and toothpaste before being fragmented and subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…These genes are all upregulated and considered as “pro-inflammatory”. Even though the extracted teeth were mechanically cleaned with a tooth brush and dentifrice, there might be some dental plaque remnants with bacterial endotoxins that are capable of eliciting an inflammatory response 48 , 49 . In support of these observations, cleaning of extracted teeth reduced but not fully abolished the inflammatory response of macrophages to ADL 49 .…”
Section: Discussionmentioning
confidence: 99%
“…These genes are all upregulated and considered as “pro-inflammatory”. Even though the extracted teeth were mechanically cleaned with a tooth brush and dentifrice, there might be some dental plaque remnants with bacterial endotoxins that are capable of eliciting an inflammatory response 48 , 49 . In support of these observations, cleaning of extracted teeth reduced but not fully abolished the inflammatory response of macrophages to ADL 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we have recently identified TGF-β as a major growth factor in ADL by a combined proteomics and RNA sequencing approach (Nasirzade et al under revision). More recently, our group, showed that ADL induces an inflammatory response when being prepared from uncleaned teeth [ 21 ]. This inflammatory response, nevertheless, was not triggered when teeth had been cleaned with toothpaste and a toothbrush [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, our group, showed that ADL induces an inflammatory response when being prepared from uncleaned teeth [ 21 ]. This inflammatory response, nevertheless, was not triggered when teeth had been cleaned with toothpaste and a toothbrush [ 21 ]. Therefore, it appears that ADL is capable of causing a strong cellular response in vitro, however, the translation of these findings into a preclinical scenario remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the mechanical removal of dental plaque significantly reduced the inflammatory reaction. 28 If a complete tooth root is used as augmentation material, as described by Schwarz et al, 9 the dimension of the root will limit the augmentation width. With the tooth shell technique described here, a larger horizontal deficit can be augmented, in analogy to the bone block grafting technique by Khoury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the preparation of the tooth also seems to have an influence on the success rate. Studies have shown that the mechanical removal of dental plaque significantly reduced the inflammatory reaction 28 …”
Section: Discussionmentioning
confidence: 99%